The growth of seedlings of rhizophoraceae in the nursery utilizing fresh water - Sarno Sarno; Moh. Rasyid Ridho (The East Java Biological Society, 2016)
The recovery of the mangrove areas that have been degraded needs mangrove seedlings in large quantity. A mangrove nursery is generally located on the land close to the planting site and brackish water. The mangrove nursery by means of fresh water is an innovation in the provision of seeds. The objective of this experiment was to determine the growth of seedlings of Rhizophoraceae in fresh water based on the parameters of the number of leaves and the height of the shoots. The method of breeding utilizes fresh water and to keep the water remains available the water circulation is regulated. The results of the observations show that the number of leaves of Bruguiera gymnorrhiza has the number of pairs of leaves compared with Rhizophora apiculata dn R. mucronata. The average height of the shoots up to the age of 5 months after planting, the highest seedlings are R. mucronata seedlings. In general, mangrove nursery with fresh water can be utilized as a means for providing seedlings for rehabilitation of mangrove.